ICTs and the possibilities for leapfrogging by developing countries. - Steinmueller, W. Edward (International Labour Review)
Though the digital divide appears to reproduce existing patterns of inequality regarding ICTs, some developing countries have narrowed the economic divide, through export-oriented production of ICTs. Certain ICT features seem to support a strategy of “technological leapfrogging” which successfully narrows gaps in productivity and output separating industrialized and developing countries. This article examines these claims, looking particularly at four difficulties in applying this strategy: acquisition of specific skills and adaption of equipment; the market conditions needed for equipment and knowledge exchange; the need to acquire complementary technologies and capabilities; and the “downstream integration requirements” to achieve the necessary market development. Reprinted by permission of the publisher.